A REVIEW ON THE CONCEPTUAL APPROACH TO AGROPRENEURIAL EDUCATION: CULTIVATING ENTREPRENEURIAL INTENTION AMONG MALAYSIAN GRADUATES - Jaffery, Nur Shahafiqah Nadiah; Syed Annuar, Sharifah Nurafizah; Abd Rashid, Muhammad Hafiz (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Agriculture is an important part of Malaysia’s economy. In recent years, more people have become interested in agropreneurship, which means starting businesses in agriculture. This paper looks at how university education can help graduates become agropreneurs by focusing on three key areas: agropreneurial curriculum, agropreneurship experiental learning, and university support. Using ideas from entrepreneurial learning theory and institutional support theory, this paper suggests ways universities can encourage students to become agropreneurs. A goo d curriculum should teach agribusiness, sustainable farming, money management, and market strategies. Agropreneurship experiental learning such as farm training, internships, and mentorship helps students apply their knowledge in real situations. Support from universities, like funding, business incubation programs, and expert advice, makes students feel more confident about starting an agro-business. This paper suggests that if universities improve their curriculum and provide more support, more graduates will choose agropreneurship as a career, helping Malaysia’s agriculture sector grow. The study can help universities, teachers, and policymakers create better agropreneurial education programs. Future research can test these ideas to see how well they work in real life.